PERFORMANCE EVALUATION OF VARIOUS IMAGE-PROCESSING TECHNIQUES FOR THE MEASUREMENT OF WATER SURFACE VELOCITY - PRADEEP P. TEMBHARE; DR. V. V. DIXIT; M. SELVA BALAN (International Journal of Innovations in Engineering Research and Technology, 2021)
Long-muffle estimation of water speed is a testing undertaking. Diverse endeavoursto gauge flight in a liquid from a smooth stream with physical contact sensors couldn't deliver precise results. Estimation of water speed with direct contact sensor which results mechanical torment and high upkeep cost. Theexpectationof this paper is to utensils the non-contact water stream speed estimation framework scilicet in light of a picture based strategy. This paper shows a methodology for assessing water stream speed by taking after the development of particles through a progression of pictures. The picture based water stream estimation recognizes the worktop elements and measures their positions regarding this present reality by using Particle Matching based on Centroid Tracking Method & Block Matching Algorithm (BMA).